Social Media Addiction and Mental Well-Being: Social Connectedness and Perceived Social Support as Serial Mediators - Kara, Berkan Can (SPRINGER, 2025)
While social media connects individuals with one another, the quality of these connections raises concerns from a mental health perspective. Examining the relationship between social media addiction (SMA) and mental well-being (MWB), as well as the key variables associated with this relationship is pertinent to mental health. This cross-sectional study addresses the serial mediating roles of social connectedness and perceived social support in the relationship between SMA and MWB. The study sample consisted of 451 adults residing in Turkey, from various occupational backgrounds, aged between 18 and 60 years (%65.19 female, Mage = 30.85 years, SD = 8.72). The data collected within the scope of the study were analyzed using a two-step structural equation modeling (SEM) approach. To determine the indirect effects, a bootstrapping analysis was conducted. The results indicated that social connectedness and perceived social support serially mediated the relationship between SMA and MWB. In the current study, it was found that high levels of SMA were associated with lower levels of MWB, contributing to the understanding of key variables related to MWB. These findings indicate that social connectedness and perceived social support are important indicators of MWB, and that considering these variables in prevention and intervention programs may be beneficial.
Keywords: Social media addiction; Social connectedness; Perceived social support; Mental well-being; HEALTH; STRATEGIES; STRESS; SCALE; SIZE; Psychology